Pengaruh Bisnis E-Commerce dan Pemeriksaan Pajak terhadap Penerimaan Pajak (Studi Kasus Wajib Pajak Yang Terdaftar di KPP Kelapa Gading) - Bagus Aprilianto; Angga Hidayat (Universitas Pamulang, 2019)
This study aims to determine the effect of e-commerce business and tax audits on tax revenue at the Kelapa Gading Tax Office. The variables that are the focus of this research are E-Commerce Business (X1), Tax Examination (X2) as Independent Variables, and Tax Revenue (Y) as Dependent Variables. This research was conducted through filling out the questionnaire by respondent. Samples were taken as many as 100 respondents, for the method of analysis and hypothesis using multiple linear regression, then the calculation uses the IBM SPSS Version 25 program, while the determination of the sample is done using the random sampling method. The results of this study indicate that the E-Commerce Business Variable has no effect on Tax Revenue. Meanwhile, the Tax Examination Variable affects Tax Revenue. Together (simultaneous) E-Commerce Business Variables and Tax Examination affect Tax Revenue. This is evidenced by a statistical test that is the calculation of the Fcount value of 22,913 with a significant level of 0,000.